Biopestisida Nabati dari Tumbuhan Tradisional Asal Gorontalo di Desa Mustika, Boalemo - Weny J A Musa; Suleman Duengo; Ahmad Kadir Kilo (Jurnal Pengabdian Pada Masyarakat, 2020)
VEGETABLE BIOPESTICIDE FROM GORONTALO TRADITIONAL PLANTS IN MUSTIKA VILLAGE, BOALEMO. Most of the villagers of Mustika are farmers who use chemical pesticides in dealing with pests that have negative effects on plants, the environment and public health, so biopesticides are needed as a substitute for these chemical pesticides. Tombili and tubile are plants that are often found in Mustika Village, and can be used as biopesticides. This method of service is through the preparation and briefing stages as well as the implementation phase of the program. In the preparation stage, an initial survey of the location of the Community Service Program is carried out. The surveyed location is in the village of Mustika, Kec. Paguyaman, Kab. Boalemo The debriefing phase of the Community Service Program Supervisor team to equip students with biopesticides. At the implementation stage the program begins with the preparation and application of rice plants. The yields obtained by the largest grain of tombili water extracted dried rice were at a concentration of 0.01%, with a dry grain weight of 7.998 kg/ha, while for tubile extract the largest weight of dry grain was at a concentration of 0.25% with a weight of dry grain as much as 9.331 Kg / Ha. For the control or untreated rice produces dry rice of 2,666 kg/ha, whereas for samples using chemical pesticides, 6,665 kg / ha of dry rice were produced.